2002
DOI: 10.1128/jvi.76.13.6825-6831.2002
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Expression in Human Gastric Carcinoma with Epstein-Barr Virus Infection

Abstract: The KT tumor is a transplantable strain of a human Epstein-Barr virus (EBV)-associated gastric carcinoma (EBVaGC), established in severe combined immunodeficiency (SCID) mice, with which the cytokine expression of EBVaGC can be investigated without interference from the infiltrating lymphocytes. As a part of a highdensity oligonucleotide array (GeneChip) analysis of EBVaGC, the interleukin-1␤ (IL-1␤) gene was the only cytokine gene that showed markedly higher expression in the KT tumor cells than in two tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…One representative gastric carcinoma cell line (MKN-1) and MKN-1 with EBV infection (EBV-MKN-1), incubated for 96 h under 0% FCS condition, were subjected to oligonucleotide microarray analysis. After the total RNA was isolated by the acid guanidium/phenol/chloroform method using TRIzol reagent (Invitrogen), oligonucleotide microarray analysis (GeneChip; Affymetrix) was carried out as described previously (22), according to the instructions from the Affymetrix GeneChip Expression Analysis Technical Manual. In Affymetrix U133plus2.0 array used here, signals from one transcript (= probe set) were measured by 11 probes, which allowed statistical evaluation for signal difference between comparative two objects.…”
Section: Methodsmentioning
confidence: 99%
“…One representative gastric carcinoma cell line (MKN-1) and MKN-1 with EBV infection (EBV-MKN-1), incubated for 96 h under 0% FCS condition, were subjected to oligonucleotide microarray analysis. After the total RNA was isolated by the acid guanidium/phenol/chloroform method using TRIzol reagent (Invitrogen), oligonucleotide microarray analysis (GeneChip; Affymetrix) was carried out as described previously (22), according to the instructions from the Affymetrix GeneChip Expression Analysis Technical Manual. In Affymetrix U133plus2.0 array used here, signals from one transcript (= probe set) were measured by 11 probes, which allowed statistical evaluation for signal difference between comparative two objects.…”
Section: Methodsmentioning
confidence: 99%
“…A subsequent in situ hybridization study of surgically resected GC showed that IL-1b is specifically expressed in vivo in EBV-associated GC. 13 Since a severe type of atrophic gastritis accompanies EBV-associated GC, 14 it is postulated that IL-1b facilitates the growth of this type of GC in the inflamed gastric mucosa. In this study on IL-1b polymorphism of the host side, however, no correlation between EBV-associated GC and IL-1b high-producer phenotypes was identified.…”
Section: Table III -Frequencies and Adjusted Odds Ratios (Or) Of 1l-1mentioning
confidence: 99%
“…4,10 Evidences for H. pylori as a causative agent for GC are primarily derived from epidemiologic data, whereas in the case of EBV, the molecular biology has proven that the virus is monoclonal even in the intramucosal carcinoma 1 and that the carcinoma develops through a specific epigenetic change, global and nonrandom CpG-methylation of cancer-related genes. 11,12 Recently, we also demonstrated that EBV-associated GC specifically produces IL-1b, suggesting that IL-1b serves as an autocrine growth factor for this carcinoma 13 in severely atrophic gastric mucosa. 14 Since there is interaction between the infective organism and the infected host, it is interesting to investigate the significance of IL-1 gene polymorphism in patients harboring GC with or without the association of EBV, and such an issue has not been investigated until recently.…”
mentioning
confidence: 99%
“…Histological studies provide evidence that immune cell iniltration was a feature of EBVaGC. For instance, iniltrating lymphocytes, containing EBV-speciic cytotoxic T cells, communicate with carcinoma cells directly, in the opposite, cytokine IL-1β was upregulated to recruit noniniltrating lymphocytes against this cell-cell contact [22,23]. Therefore, in EBVaGC, immune responses in tumor microenvironment also accompany with the progression of EBVaGC [24].…”
Section: The Risk Factors Of Gcmentioning
confidence: 99%